Synchronisation and chaos in a laser diode driven by a resonant tunnelling diode - Romeira, Bruno (2012)
The authors report on a hybrid integration of a resonant tunnelling diode laser diode driver configuration that can operate as a self-oscillating circuit, and when externally perturbed shows regions of frequency division and frequency multiplication, quasi-periodic and chaotic oscillations, both in the optical and electrical outputs. The authors also demonstrate that this optoelectronic circuit is well described as a Lie´nard’s oscillator. The synchronisation capabilities of the circuit have potentially novel functions for optical communications systems including clock recovery, clock division and data encryption.